Pengaruh Kinerja Keuangan Terhadap Return Saham Perusahaan Pertambangan : Sektor Industri Batubara Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2021 - Nurul Fajri Arif; Pra Gemini; Arianto Taliding (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the effect of Earning per Share (EPS), Return on Assets (ROA), Return on Equity (ROE), Current Ratio (CR), Deb to Equity Ratio (DER), Price to Book Value (PBV) on Returns. Share. The object of this research is the Indonesian Stock Exchange, mining companies in the coal industry sector for the 2019-2021 period. The research data used is secondary data with the sampling method using non-probability sampling. And the data analysis method is by calculating financial performance, determining stock returns using a sample of 19 companies. The results of this research have been tested on classical assumptions in the form of normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests as well as hypothesis tests in the form of t tests, f tests , determination test, and multiple linear regression test. The results of this study show that ESP partially has a negative effect on Stock Return, ROA partially has a positive effect on Stock Return, ROE partially has a negative effect on Stock Return, CR partially has a positive effect on Stock Return, DER partially has a positive effect on Stock Return, and PBV partially has a negative effect on Stock Return.